2014
DOI: 10.1002/2014ja019894
|View full text |Cite
|
Sign up to set email alerts
|

Solar rotation effects on the Martian ionosphere

Abstract: We present a detailed investigation of the solar rotation effects on the Martian high-latitude (~63°N-81°N) ionosphere using the electron density (N e ) data measured by Mars Global Surveyor and solar XUV and EUV fluxes measured by SOHO under high (2000SOHO under high ( -2001SOHO under high ( ), medium (2003, and low (2005) solar activity conditions. A fast Fourier transform spectral analysis method is used to estimate the amplitude of the rotation period in these parameters. This method clearly reveals the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
(100 reference statements)
1
15
0
Order By: Relevance
“…For comparison, 10 profiles observed on 2 January 2005 when ionospheric main peak heights reach the maximum were selected to show the status of the Martian ionosphere at the peak of the abnormal event; these are referred to as "Storm Day" profiles. To show the status of the Martian ionosphere clearly, the electron density profiles are averaged to get a daily mean profile with the method used in the previous study (Venkateswara Rao et al, 2015). Figure 4 shows the daily mean profiles on Start Day or called Pre-storm Day (dash-dot line) and Peak Day or called Storm Day (solid line) between 100 and 180 km with 1-km height resolution.…”
Section: Observations Of the Ionosphere From The Mgs/rs During The Dumentioning
confidence: 99%
“…For comparison, 10 profiles observed on 2 January 2005 when ionospheric main peak heights reach the maximum were selected to show the status of the Martian ionosphere at the peak of the abnormal event; these are referred to as "Storm Day" profiles. To show the status of the Martian ionosphere clearly, the electron density profiles are averaged to get a daily mean profile with the method used in the previous study (Venkateswara Rao et al, 2015). Figure 4 shows the daily mean profiles on Start Day or called Pre-storm Day (dash-dot line) and Peak Day or called Storm Day (solid line) between 100 and 180 km with 1-km height resolution.…”
Section: Observations Of the Ionosphere From The Mgs/rs During The Dumentioning
confidence: 99%
“…These temporal variations result from the changing heliocentric distance (∼1.38–1.67 AU), the planet's obliquity (determining the local season), and the changing solar radiation itself. Both solar rotation (∼27 day periodic changes in the solar output) and solar cycle (∼11 year periodic overall changes in solar output) variations of the solar X‐ray and EUV fluxes are significant (up to factors of ∼3 to 100, depending on the wavelength [ Woods and Rottman , ]), producing dramatic variations in global thermospheric temperatures, composition, and winds [e.g., Bougher et al , ; Forbes et al , ], as well as ionospheric densities [e.g., Fox , ; Venkateswara Rao et al , ]. Thus, significant variability of the Martian thermosphere and ionosphere system is directly linked to the variability of the solar EUV‐UV fluxes received at Mars.…”
Section: Introductionmentioning
confidence: 99%
“…The ionosphere of Mars is known to exhibit periodicities related to the solar rotation (Nielsen et al, 2006;Rao et al, 2014), and its variability as a function of the solar cycle was also reported (Sánchez-Cano et al, 2015;Withers, Vogt, et al, 2015). Crustal magnetic fields can also influence the electron densities, in particular at high altitudes (Andrews et al, 2014;Němec, Morgan, Gurnett, & Andrews, 2016).…”
Section: Introductionmentioning
confidence: 99%